MODEL PEMBERDAYAAN MASYARAKAT MINANGKABAU DITINJAU DARI ASPEK EKONOMI - Iswadi, Iswadi; Fadri, Zainal (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to examine the economic empowerment model applied by the Minangkabau community, which is known as a society that holds firmly to values, traditions, culture and religion, besides that Minangkabau people have long been known as Minang merchants who adhere to a communal economic system. The cooperative economic system implemented by the Minangkabau community is able to maintain the economic stability of the Minangkabau community, it is necessary to conduct a study to see the model of economic empowerment of the Minangkabau community. The research method used is library research by collecting data through reference books, published scientific journals and other literature to see the applied economic empowerment model. The data collection method is carried out by collecting study materials, reading, making research notes and reviewing study materials related to the research focus. The findings of this study are that the Minangkabau community's economy is stable and able to withstand economic shocks by applying several models of economic empowerment, namely mutual cooperation, cooperation, wandering and trading.